Professionnalisation ou déprofessionalisation: Une base conceptuelle pour l’évaluation de la competence en psychologie - Perron, Jacques; Gendreau, Pierre; Lecomte, Conrad (Canadian Journal of Counselling and Psychotherapy, 2012)
Accountability for psychological services has raised the question of competence in professional psychology. It is suggested that the concepts of professionalization and deprofessionalization may prove to be useful in understanding what professional psycholgy, particularly in the province of Quebec, has done with the question of competence in the past as well as what it is going to do in the future. Elements of professionalization—systematic body of theory, social recognition, monopoly, degree of organization—are presented and applied to the development of professional psychology in Quebec. The concept of deprofessionalization is also introduced as an alternative basis for the evaluation of competence in professional psychology.